Discovery of a distinct type of methylenetetrahydrofolate reductase family that couples with tetrahydrofolate-dependent demethylases - HongYang Yu; Naofumi Kamimura; Ryo Kato; Michelle Jane Genoveso; Miki Senda; Eiji Masai; Toshiya Senda (Communications Biology)
Abstract Methylenetetrahydrofolate reductase (MTHFR) is a key enzyme in one-carbon (1C) metabolism, catalyzing the reduction of methylenetetrahydrofolate to methyltetrahydrofolate. Interestingly, Sphingobium lignivorans SYK-6, a model bacterium for the catabolism of lignin-derived aromatic compounds, possesses a unique MTHFR (S6MTHFR) that catalyzes the reverse reaction of typical MTHFRs—namely, the oxidation of methyltetrahydrofolate. However, no direct evidence supports this function. Here, we show that S6MTHFR catalyzes the oxidation of methyltetrahydrofolate and elucidate the molecular mechanism underlying the unique enzymatic properties of S6MTHFR based on its crystal structure. Furthermore, a database search reveals that a group of bacteria, including S. lignivorans SYK-6, utilize tetrahydrofolate-dependent demethylases to produce methyltetrahydrofolate, which is subsequently oxidized by an S6MTHFR-type enzyme. We propose that the combination of a demethylase with an S6MTHFR-type enzyme represents a distinct type of 1C metabolism that may regulate methionine biosynthesis.